International banking strategic alliances : - Itschert, Jorg (Palgrave/Macmillan, 2003)
The European Union is an increasingly important influence on our daily lives with important political, economic and cultural implications. To understand how to bridge the gaps between national cultures and economic systems is an imperative. This book considers in depth from the inside out, one such Franco-German collaboration in the banking sector and sheds light on these imperatives. The practitioner-academic collaboration provides detailed insights into a real cross-border alliance in an accessible manner.